Assessment of clinical spectrum of thrombocytopenia and its association with different disease states reported in Dow Diagnostic Reference and Research Lab (DDRRL) - Abbas, Farah Fatima; Kouser, Shaheen (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the relevance of thrombocytopenia to other disease states in patients reporting at a haematology laboratory. Method: The cross-sectional, retrospective study was conducted at the Dow Diagnostic Research and Reference Laboratory of the Dr Ishrat ul Ebad Khan Institute of Blood Diseases, Down University of Health Sciences, Karachi, and comprised data from the blood bank and haematology laboratory related to patients who visited during October 2021to August 2022. Data was analysed using SPSS 26. Results: Of the 1,249 patient with mean age 38.5±19.7 years (range: 0-89 years), 79(6.3%) were aged <12 years, 592(47.4%) were aged 12-40 years and 578(46.3%) were aged >40. Most of the patients were males 793(63.5%), and 604(48.4%) had Grade 1 thrombocytopenia. Among the females, Grade 1 thrombocytopenia was found in 246(53.9%) and Grade 2 in 140(30.7%) patients compared to 358(45.1%) and 222(28%) in males, respectively (p<0.05). Association between thrombocytopenia and diagnoses was not significant (p>0.05). Conclusion: Thrombocytopenia was found to be strongly associated with gender. Key Words: Thrombocytopenia, Bleeding, Dengue, Malaria.